An Urgence To Establishing Regulations For Implementing State Administrative Justice Law - Sri Rahayu; Siti Rhodiyah Dwi Istinah (Universitas Islam Sultan Agung, 2021)
This study aims to examine and analyze why an implementing regulation is needed for Act No. 51 of 2009 concerning the Second Amendment to Act No. 5 of 1986 concerning the State Administrative Court. The research method used is descriptive qualitative research with a normative juridical approach that examines theories, legal principles and related legislation. The method of data collection was carried out by library research with the type of research data consisting of primary, secondary, and tertiary legal materials. The government needs to immediately establish implementing regulations for the State Administrative Court Law to provide legal certainty for the community,